A preclinical method for evaluating the kinematics of knee prostheses. (April 2019) - Wang, Xiao-Hong; Dong, Xiang; Zhu, Bao-Zhang; Jiang, Lei; Jin, Zhong-Min; Suguro, Toru; Cheng, Cheng-Kung
Highlights: This study introduces a testing method for recording movements of the knee joint. A novel testing jig was developed to track the medial and lateral movements. The test system developed in this study required many factors to be validated. The system developed in this study is a direct and reliable in vitro test method. Abstract: The primary intent of anatomical knee implants is to replicate the motions of a normal knee joint. In developing such designs, a preclinical evaluation of kinematic behavior is needed. This study introduces an in vitro testing method for recording movements of the knee joint. A novel testing jig was developed and incorporated into a knee simulator setup alongside a motion capture system to directly track the medial and lateral movements of a knee prosthesis. The test system developed in this study required a number of factors to be validated; (i) gait inputs to the knee simulator (result: 0.37–1.575% error), (ii) validity of global coordinate system in the motion capture system, (iii) the position of flexion facet centers (FFCs) detected by the motion capture system (result: a maximum error of 0.08 mm in AP direction and 0.3 mm in SI direction), (iv) local coordinate system in the motion capture system (result: 1.09% error for the measurement of flexion angle), (v) that FFC results were in good agreement with inputs. In conclusion, the system developed in this study for recording FFC is a direct and reliable in vitro test method for analyzing the kinematics of a knee prosthesis.